2013
DOI: 10.7494/geol.2013.39.4.317
|View full text |Cite
|
Sign up to set email alerts
|

An attempt to identify traffic related elements in snow

Abstract: Abstract:The main objective of this article is an attempt to use snow as an indicator in the process of assessing and identifying vehicle-derived elements pollution. The aim of the present study is to characterize traffic-related elements in snow collected from three sites: a parking place, a highway and a relatively unpolluted airfield. Several recent studies suggest that road traffic is considered to be one of the major sources of environmental pollution in urban areas. In order to avoid the problem of low e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
8
0
1
Order By: Relevance
“…Higher content of solid particles in snow cover at the MO MSU leads to the increase in CF values for Zn, Mo, Cr, Sr, V, Pb, and Ca up to 10-16, as compared with the yards where CF values of these MMs are 5-9. High levels of Zn at the MO MSU are probably due to the influence of transport, since car parking lots are located nearby, where intense accumulation of the metal is typical [106]. Our studies on the chemical composition of dust component in snow cover of the eastern industrial part of Moscow showed that the following MMs are the ones that accumulate most intensively (the CF value is written in subscript): Mo 19 Sb 4.9 As 4.6 W 4.3 Sn 3.6 V 2.1 Fe 2.1 Cr 2.0 [46].…”
Section: Suspended Forms Of Mmsmentioning
confidence: 99%
“…Higher content of solid particles in snow cover at the MO MSU leads to the increase in CF values for Zn, Mo, Cr, Sr, V, Pb, and Ca up to 10-16, as compared with the yards where CF values of these MMs are 5-9. High levels of Zn at the MO MSU are probably due to the influence of transport, since car parking lots are located nearby, where intense accumulation of the metal is typical [106]. Our studies on the chemical composition of dust component in snow cover of the eastern industrial part of Moscow showed that the following MMs are the ones that accumulate most intensively (the CF value is written in subscript): Mo 19 Sb 4.9 As 4.6 W 4.3 Sn 3.6 V 2.1 Fe 2.1 Cr 2.0 [46].…”
Section: Suspended Forms Of Mmsmentioning
confidence: 99%
“…The most significant source of salinity of urban soils is undoubtedly the salt use for road de-icing, but other sources should not be neglected, and these include: mining and salt and sulphur processing, combined heat and power plants burning saline and sulphated coal, bottom waters of metalliferous ore and bituminous coal mines, car transportation, municipal management, hardening of roads and squares using slag, leachates from industrial waste landfills or heaps (e.g. from the closed Sodium Solvay Factory in Krakow), excessive fertilisation of urban green areas or gypsum ingress into soil (Adamiec et al 2013, Jakubiak & Urbański 2015, Vargas et al 2018. 1 Planty Gardens are located within the first ringway (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Most often these are ferrocyanides, and their degradation releases the toxic cyanide ion CN − (Novotny et al 1998, Kelly et al 2008. Apart from that, the soil is also polluted with heavy metals and other substances accompanying de-icing agents, which penetrate the soil and ultimately pollute the water and soil environment (Novotny et al 1998, Bäckström et al 2004, Adamiec et al 2013 and elevated salinity can additionally lead to the release of previously adsorbed heavy metals and enhance their transport to surrounding area (Findlay & Kelly 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Estos métodos de evaluación fueron utilizados para valorar cuantitativamente la influencia de actividades antrópicas sobre la concentración de MP en el SV, a partir de concentraciones de fondo geoquímico o elementos que por su abundancia no se pudieron ver influenciados por factores externos; como por ejemplo las fuentes de contaminación relacionadas con el tráfico vehicular [51], [52]. Los métodos detectados para una evaluación individual fueron el factor de contaminación (Cf), factor de enriquecimiento (EF), e índice de geoacumulación (Igeo); y los métodos detectados para una evaluación a nivel de multielemento fueron el grado de contaminación (Cdeg) e índice de carga de contaminación (PLI) (Tabla 5).…”
Section: Enriquecimiento Metálicounclassified